Bone marrow-derived mononuclear cells therapy for ischemic stroke - Petru Butucel; Viorel Nacu; Vitalie Lisnic (The Moldovan Medical Journal, 2019)
Background: Nowadays, the cerebrovascular event is the second cause of death and the third cause of disability worldwide. In the last few decades, stem cell-based approaches are widely analyzed as a potential treatment for this disease. One of these types of cells are bone marrow-derived mononuclear cells (BMMNCs). In this review, we analyzed 9 completed clinical trials with the use of BMMNCs in patients with ischemic stroke, which we found in the clinicaltrials. gov and PubMed databases, using the keywords “stroke“ and “bone marrow mononuclear cells”. Our goal was to analyze the safety and efficiency of this therapeutic approach, as well as the optimal therapeutic time window, transplantation route and cell dose used. The best stroke phase to apply this therapy is the subacute stage. Higher numbers of CD34+ cells, derived from BMMNCs were correlated with a trend toward a better outcome. All the clinical trials support the idea that BMMNCs transplantation is a safe therapy. Conclusions: In conclusion the author points out that the autologous transplantation of BMMNCs is harmless and not associated with severe complications. Although some clinical studies stated a better outcome in patients treated with BMMNCs, further clinical trials are needed to establish their therapeutic efficiency.